He loves me! Learning to live in the Father's affection - Jacobsen, Wayne 1953- (Newbury Park, CA Windblown Media, 2007)
Describes how one can discover a transformative relationship with God by realizing that God's love is not something that is earned but instead is unconditional and everlasting
Scripture quotations from the Holy Bible, New International version
Archivierung prüfen
Keywords: God -- Attributes; Christian Life; Religious Life; Conduct of life